2009
DOI: 10.1017/s1751731108003509
|View full text |Cite
|
Sign up to set email alerts
|

Feeding grape seed extract to horses: effects on health, intake and digestion

Abstract: A feeding trial involving four Thoroughbred race horses was undertaken to establish whether inclusion of grape seed extract (GSE) in the diet of horses undergoing mild exercise had any effects on their general health, intake and digestion. Supplementation with GSE had no effect on either feed or water intake of the horses and the supplement was readily palatable to the horses at all levels of inclusion. Feeding GSE caused no adverse effects in terms of animal health (temperature, pulse and respirations rates),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…The inclusion of DGP had no effect on the feed intake of horses. These findings are similar to those in other animal studies where DGP or grape seed extract was fed (Davies et al 2008;Ishida et al 2015;Aditya et al 2018).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The inclusion of DGP had no effect on the feed intake of horses. These findings are similar to those in other animal studies where DGP or grape seed extract was fed (Davies et al 2008;Ishida et al 2015;Aditya et al 2018).…”
Section: Resultssupporting
confidence: 91%
“…Currently, only few references in the literature regarding the use of grape by-products in horse diets are available (Davies et al 2008) and information from other animal studies is limited, while found results are inconsistent. Digestibility improvement of CP, ADF and NDF due to the grape pomace powder inclusion was reported by Foiklang et al (2016) in dairy steers.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, only few references in the literature regarding the use of grape by-products in horse diets are available and information from other animal studies is limited. Davies et al (2009) recorded a positive effect on fermentation in hindgut of Thoroughbred race horses when 150 mg of grape seed extract/kg BW was fed. Kolláthová et al (2020) reported an indication of better dry matter, organic matter and crude protein digestibility in sport horses fed 200 g of DGP; however, 400 g of DGP in horse diets affected the utilisation of nutrients negatively.…”
Section: Resultsmentioning
confidence: 97%
“…Grape by-products have already been used in several animals breeding, testing the qualities they provide [ 20 ]. The species more frequently used were dairy cows [ [21] , [22] , [23] ], dairy ewes [ [24] , [25] , [26] ] horses [ 27 , 28 ] and rabbits [ [29] , [30] , [31] ].…”
Section: Introductionmentioning
confidence: 99%